Diversity of hemerobiids (Neuroptera) and associations with preys in coffee plants - Lara, Rogéria Inês Rosa; Perioto, Nelson Wanderley; de Freitas, Sérgio (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the diversity of Hemerobiidae (Neuroptera) in coffee and its relationships with Leucoptera coffeella, Coccus sp., Planococcus sp., Oligonychus ilicis, Brevipalpus phoenicis, Aphis spiraecola and Toxoptera aurantii. The specimens were collected in Cravinhos, São Paulo state, Brazil, between May 2005 and April 2007. The hemerobiids were collected with sweeping nets, and light and Möricke traps. Coffee leaves were collected for prey sampling. A total of 882 hemerobiids were obtained: Nusalala tessellata (467 individuals, 52.9% of the hemerobiids collected), Hemerobius bolivari (153, 17.3%), Megalomus impudicus (114, 12.9%), Sympherobius miranda (109, 12.4%), Megalomus rafaeli (30, 3.4%), Sympherrobus ariasi (6, 0.7%) and Nomerobius psychodoides (3, 0.3%). Occurrence of Nusalala tessellata and M. impudicus showed significant positive correlations with Coccus sp. presence; the same fact occurred to M. rafaeli and L. coffeella larvae with A. spiraecola, and H. bolivari with O. ilicis. The correlations were negative and significant between occurrence of S. miranda and O. ilicis, and between N. tessellata and L. coffeella larvae and O. ilicis.